EDUGAME MAKAN SEHAT SEBAGAI UPAYA PENCEGAHAN DINI PENYAKIT TIDAK MENULAR PADA SISWA SD - Izzatul Arifah; Afifah Nurhafni Ayati; Kirana Haura’ Arie Prasastywy; Very Rizkia Dewiyanti; Erin Tri Cahyanti (Jurnal Berkawan: Jurnal Pengabdian kepada Masyarakat, 2025)
Non-communicable diseases (NCDs), the leading cause of death worldwide, require early preventive efforts through the promotion of healthy lifestyles in school settings. A situational analysis in Karangwuni Village, Weru, Sukoharjo, identified a high prevalence of hypertension, with limited early prevention focused on unhealthy eating patterns. Although SD N 1 Karangwuni has a dokter kecil program, nutrition-related health education remains minimal. This community service activity aimed to improve students’ knowledge through healthy food edugames as an early NCD prevention strategy. The activity involved 36 students and was conducted in three sessions: education, discussion, and games. The results showed high participant enthusiasm and a significant increase in knowledge after the intervention. Educational media in the form of a healthy food card game set was provided to the school’s UKS to support program sustainability.